Voltaire historiographer - Pierse, S (Voltaire Foundation, 2017)
Voltaire’s historical works reflect his own changing roles and preoccupations from conteur to campaigner. His groundbreaking historical output of thirty-eight texts, composed throughout his long career as a writer, is now receiving renewed critical attention. In the first study to explore the whole range of Voltaire’s writings in this domain, Síofra Pierse looks at the irreducible ambiguity of the term histoire, both factual truth and the way it is represented – ‘history’ and ‘story’. She discusses how Voltaire’s theories of history interact with other, more literary considerations, and analyses how a search for truth overlaps with a desire to create a compelling narrative that engages the reader in a deeper, collaborative, and polemical project. In Voltaire historiographer: narrative paradigms, Síofra Pierse brings to light how the philosophe exploits the potential of history not simply to record the past, but to influence the present and shape the future. Acknowledgements List of abbreviations Introduction: Historiographerie I. Narrative 1. The historiographer 2. The author 3. The reader II. Story 4. Digressions 5. Heroics III. Truth 6. Fact and fable 7. Truth and doubt Conclusion: beyond history Appendix: Corpus summary Bibliography Index